147k views
0 votes
What is the rational expression as a sum of partial fractions?

What is the rational expression as a sum of partial fractions?-example-1
User Lazyhammer
by
5.1k points

1 Answer

4 votes


(-x^2+2x-5)/(x^3-x^2)

Rewrite the expression as:


(-x^2+2x-5)/(x^2(x-1))

The partial fraction expansion is of the form:


(-x^2+2x-5)/(x^2(x-1))=(A)/(x-1)+(B)/(x)+(C)/(x^2)

Multiply both sides by x²(x - 1):


\begin{gathered} -x^2+2x-5=Ax^2+(x-1)(Bx+C) \\ -x^2+2x-5=-C+(A+B)x^2+(C-B)x \end{gathered}

Equate the coefficients on both sides:


\begin{gathered} -5=-C_{\text{ }}(1)_{} \\ 2=C-B_{\text{ }}(2) \\ -1=A+B_{\text{ }}(3) \end{gathered}

So, from (1):


C=5

Replace C into (2):


\begin{gathered} 2=5-B \\ B=3 \end{gathered}

Replace B into (3):


\begin{gathered} -1=A+3 \\ A=-4 \end{gathered}

Therefore, the answer is:


(-x^2+2x-5)/(x^2(x-1))=(-4)/(x-1)+(3)/(x)+(5)/(x^2)

User Alesh Houdek
by
5.4k points